Regulatory encounters : multinational corporations and American adversarial legalism - Axelrad, Lee, 1963-; Kagan, Robert A. (California series in law, politics, and society, 2000)
This work reports on a path-breaking study of how government regulation of business in the United States differs in practice from regulation in other economically advanced democracies. In each of ten in-depth case studies, the contributors to this volume compare a particular multinational corporation's experience with parallel regulatory regimes in the United States and in Japan, Canada, Great Britain, Germany, the Netherlands, and the European Union, noting precisely which regulatory precautions were actually implemented in each country.